Penerapan Model Pembelajaran SAVI untuk Meningkatkan Hasil Belajar IPA Siswa Kelas V Sekolah Dasar - Wardani, Fitrian Prila (PANCAR, 2017)
Somantic Audio Visual Intellectual (SAVI) is a learning model that uses all senses to improve learning activities (Meiere, 2005). The purpose of this research is to improve the science learning outcomes of fifth grade elementary school students using the SAVI learning model. The sample used in this research was the fifth grade students of Cihonje 2 Elementary School, Gumelar District, Banyumas Regency with a total of 25 students. This research is a classroom action research. The research procedure consists of four stages, namely planning, implementation and reflection. The results of this research indicate that an average increase in cycle I was 44%, which means that 11 of the 25 students were completed. In cycle II there was an increase of 92%, which means 23 out of 25 students who completed the science learning. Based on the results of the research it can be concluded that the application of the SAVI learning model can improve the learning outcomes of the fifth grade students of fifth grade students of Cihonje 2 Elementary School.?Keywords:.